Comparing the Efficacy of Feed Withdrawal and Corn Diet Systems for Induced Molting on Health and Performance of Broiler Breeder Flocks - Khalf, Mahmoud A.M.; Ismael, Elshaimaa; Bawish, Basma M. (Journal of Advanced Veterinary Research, 2023)
This study was conducted to compare the effectiveness of two induced molting methods (The modified California method and the reduced nutrient method) and to determine the preferable method that achieves the main goals of post-molt in breeder hens. Twenty-four commercial Ross broiler breeder flocks (59 weeks old) were used. The birds were divided into two groups (12 flocks each). Group 1 (G1) was subjected to a modified California forced molting method, while Group 2 (G2) was subjected to a reduced-nutrient method (low-protein low-energy diet). Body weight (BW), weight loss, mortality, and egg production cease were determined before the molting period, while feed intake (FI), body weight gain (BWG), mortality, egg production, fertility, and hatchability% were recorded after molting. The results of this study indicated that, although the California treatment ceased egg production earlier than the reduced nutrient molting method (day 8 and day 14) respectively, and the weight loss achieved after 28 d in the California method (28.7%) versus (30.4% after 36 days) in the reduced-nutrient system. The reduced nutrient system showed a lower mortality rate and a higher BW at the start and the end of the molting period. Additionally, the reduced nutrient system showed enhanced post-molt performance, as demonstrated by improved BWG, lower mortality%, higher egg production% (79.1%) versus (74.5%) in the California group, and better hatchability%. The FI and fertility% not significantly affected between the different groups. Â In conclusion, forced molting by the reduced-nutrient method achieved the main goals of induced molting and recorded the best values in productive traits in the post-molt period. So, it can be used as a viable alternative to the feed withdrawal method for the successful induction of molting from both the economic and welfare points of view.